ANALYSIS OF THE VARIETY OF EYE IMPAIRMENTS IN GLAUCOMA CASES IN CHILDREN AND ADULTS - Tsvetomir Dimitrov (Peytchinski Publishing, 2017)
Glaucoma is a disease, which results in definitive vision reduction. The aim of this study is an analysis of the differences in eye impairments in connection with the progression of glaucoma in different age groups (children and adults). A documentary method of investigation of scientific sources, based on clinical practice, is applied. The methodology of the study comprises investigation of causes and manifestations of the disease and its typology. The specific variety in the manifestation of glaucoma is established in children and adults. Excavation of the optic nerve occurs in the adult persons, because the eyeball is already thickened, and collagen is dense. The eye begins to swell in children because the tissues are more loose; the eyeball becomes bigger, and enlargement of cornea and sclera occurs. Children and adults with the diagnosis of glaucoma have a different way of eye impairment. The early establishment and identification of symptoms prevent from the progression of the losses in the visual field, and from blindness, by means of appropriate treatment.